Plasmachemical Synthesis and the Assessment of the Thermal Conductivity of Fuel Compounds "UO2-MgO"; AIP Conference Proceedings; Vol. 2101 : Isotopes: Technologies, Materials and Application (ITMA-2018) - Shamanin I. V. Igor Vladimirovich; Karengin A. G. Aleksandr Grigorievich; Karengin A. A. Alexey Alexandrovich; Novoselov I. Yu. Ivan Yurievich; Poberezhnikov A. D. Andrey Dmitrievich; Alyukov E. S. Evgeny Sergeevich (2019, 2019)
Title screen